Perineal colostomy: an option in the treatment of inferior rectal and anal canal cancer - Gama,Luciano P. Nogueira da (2014)
INTRODUCTION: The surgical treatment of anorectal cancer is considered a challenging topic. Colostomy, temporary or permanent, can be a serious limiting factor with respect to the quality of life of cancer patients. Our goal is to study the clinical and surgical experience in patients with anorectal cancer, in whom we proceeded to abdominoperineal resection with a perineal colostomy at the anterior border of the incision resulting from the amputation of the rectum.METHODS: The medical records of patients undergoing abdominoperineal resection with perineal colostomy from January 1st, 1998 to July 1st, 2012 were analyzed retrospectively.RESULTS: Twenty-seven patients were studied; 15 (55.56%) were male and 12 (44.44%) females, with a mean age of 56.3 years. The average length of hospital stay was 7.4 days. Complications included four (14.8%) prolapses of the perineal colostomy, which were surgically treated after the sixth month postoperatively, two (7.4%) partial suture dehiscences of the perineal colostomy, treated with hyperbaric oxygen therapy, two (7.4%) stenoses of the perineal colostomy, treated with dilation, two (7.4%) incisional hernias and one (3.7%) urinary incontinence.CONCLUSION: The perineal colostomy is a relatively new proposition, with acceptable morbidity rates. We understand that the perineal colostomy dismisses the use of a collection device, leaves no odor and allows the periodic application of enemas for colon cleansing, which prevents stoma incontinence. Another advantage is to enable the patient's return to a good social and work interaction; thus, it will be possible his (her) reintroduction into society.